Advanced practice nurses’ scope of practice: a qualitative study of advanced clinical competencies - Anna‐Lena Nieminen; Bodil Mannevaara; Lisbeth Fagerström (2011)
Scand J Caring Sci; 2011; 25; 661–670 Advanced practice nurses’ scope of practice: a qualitative study of advanced clinical competencies Aim To describe and explore Advanced Practice Nurses’ clinical competencies and how these are expressed in clinical practice. Background Discussion concerning advanced clinical practice has been ongoing in the USA since the 1960s and in the UK since the late 1980s. Approximately 24 countries, excluding the USA, have implemented the role of Advance Practice Nurse (APN). In the Nordic countries, especially Sweden and Finland, APNs have been introduced in some organizations but their competency domains have not yet been clearly defined. Theoretical framework The study’s theoretical framework emanates from Aristotle’s three‐dimensional view of knowledge that is epistêmê, technê, and phronesis. Methods Between October 2005 and January 2006, focus group interviews of Clinical Nurse Specialists who provide expert functions in pediatric, internal medicine, and surgical units (n = 26) and APN students (n = 8) were conducted. The data material was analyzed using inductive content analysis. Findings Grouped into five main themes, the study results indicate that APNs possess advanced level clinical competencies in: (A) assessment of patients’ caring needs and nursing care activities, (B) the caring relationship, (C) multi‐professional teamwork, (D) development of competence and nursing care, and (E) leadership in a learning and caring culture. Conclusion Clinical competencies consist of advanced skills, which typify an expanding role that offers new possibilities for holistic patient care practice. APNs’ scope of practice is characterized by responsibility and competence in making autonomous judgments based on expanded clinical competence. On an advanced level, clinical competence consists not merely of advanced skills for assessing and meeting the needs of patients but also the creation of safe and trustful relationships with patients and collaboration with colleagues. APNs can realize advanced skills in their actions through their manner of knowing, doing, and being.